A case for complexity-informed participatory action research with young people. (July 2022) - Crook, Deborah J; Cox, Pat
This article addresses the fundamental issue of using qualitative research methods that encourage young people's participation in settings that more commonly promote neoliberalism at the expense of social justice. Through a case study in an English primary school, it demonstrates how complexity-informed participatory action research could be advanced to enable young people's participation rights, by building intergenerational relationships that reposition young people and adults within systems and by revealing local and global complexities involved in conceptualising transformational resistance. The developing method is discussed providing an original contribution to knowledge and practice in research with young people, with potential to reconcile schooling and socially just strategy.